Effectiveness of Partial Body-Weight Supported Treadmill Training-Audio Cues and Traditional Overground Walking in Improving Gait Speed and Cardiorespiratory Fitness After Stroke - Hening Laswati; Meisy Andriana; Ida Yuanita (Indonesian Journal of Physical Medicine & Rehabilitation, 2015)
Objective: To compare the effectiveness of Partial Body-Weight Supported Treadmill Training-Audio Cues (PBWSTT-AC) and the traditional over ground walking in improving gait speed andcardiorespiratory fitness after stroke.Methods: pretest-posttest control group design of patients with sub-acute and chronic ischemicstroke who came to Physical Medicine and Rehabilitation (PMR) Department of Dr. Soetomo andAirlangga University Hospital Surabaya. Patients with onset 3 weeks until 10 years, age between 21until 70 years old, able to walk independently for 6 minutes, sufficient vision and hearing and canfollow simple instructions were included in this study. There were 18 patients at beginning and 16patients completed the study. Patients underwent walking exercise for 20 minute, 3 times a week for12 sessions. PBWSTT-AC group received metronome auditory rhythmic stimulation, while controlgroup received traditional walking exercise with customized speed according to patient’s preference.Gait speed were assessed by 10 meter Walk Test and cardiopulmonary endurance counted fromresting heart rate.Results: There were improvements in gait speed and cardiorespiratory fitness within each subjectgroup. Traditional group showed significantly larger increases in fast gait speed (p=0.023) but notin self-selected gait speed (p=0.002). PBWSTT-AC group showed significantly larger decreases(p=0.002) in resting heart rate (p=0.003).Conclusion: PBWSTT-AC was not shown to be superior to traditional walking in improving gaitspeed, but superior in improving cardiorespiratory fitness. Further study are needed to evaluate thelong-lasting effect of using PBWSTT-AC in improving cardiorespiratory fitness.Keywords: Partial Body-Weight Supported Treadmill Training-Audio Cues, gait speed, cardiorespiratory fitness